Prevalencia del virus de Leucemia Felina en gatos domésticos en las parroquias urbanas del cantón Latacunga – Cotopaxi. - Vasco Villamarin, Anthony Damian (2022)
Feline Leukemia Virus (FeLV) is a highly contagious disease that affects domestic cats of any age, although its incidence is higher in its juvenile stage, however early diagnosis and timely treatment improve the cat's quality of life, therefore research was conducted in the urban parishes of Latacunga Cotopaxi canton with the main objective of assessing the prevalence of Feline Leukemia, to know the current situation of FeLV in the canton since there is no previous information. The data for the development of the research were obtained from clinical records of cats with symptoms of FeLV stored in Veterinary Centers, where 170 suspected cases were found, of these cases in 81 were used a diagnostic test (Immunochromatography, ELISA, PCR) to confirm the presence of the pathology of these 63 are positive and 18 negative. When analyzing the data, a real prevalence of 95.33% of Feline Leukemia in the canton Latacunga of suspected cases is determined, the parish San Buenaventura has a higher prevalence and the year in which there was a higher prevalence was from 2015 to 2019 without taking into account 2016 since no information was found in this year. Body condition, coexistence with animals in the home, sexual status and if they have vaccines with a p value (<0.05) are risk factors that are associated with the presence of the disease.